Response surface method optimization of synthesized superparamagnetic magnetite (Fe3O4) nanoparticles characterized by pulsed IR calibration-free laser-induced breakdown spectroscopy - Tajabadi, Maryam; Khosroshahi, Mohammad E.; Alanagh, Hamideh Rezvani (Applied physics. A, Materials science & processing, 2023)
Magnetite nanoparticles (Fe 3 O 4 ) are the subject of numerous investigations, particularly regarding synthesis conditions. In this study, we used the Response Surface Method (RSM) to optimize Fe 3 O 4 synthesis conditions by modifying the concentration of iron salts, oxidizing medium and reaction temperature. The samples were characterized by Field Emission Scanning Electron Microscope (FESEM), Vibrating Sample Magnetometer (VSM), X-ray Diffraction (XRD), and Transmission Electron Microscopy (TEM). Ten experimental runs with two independent variables and one categorical variable were proposed using the three-level-three-factor design. The results were statistically analyzed using ANOVA. The analysis confirmed that the response variables were significantly influenced by factors A (concentration of iron), B (concentration of the alkaline), A 2 , and B 2 with a p value less than 0.05. In this work, the Adequate Precision i.e., the signal-to-noise ratio, which should be more than four, were 20.50 and 24.48 for both models indicating an adequate signal to explore the design space. The optimized condition for the smallest particle size with the highest saturation magnetization of 60 emu/g was determined using 0.012 M of iron salts, 0.9 M of an alkaline medium concentration, and a reaction temperature of 70 °C. The mean particle size of nanoparticles was about 9.8 ± 1 nm using the Digitizer Image Analysis software. The calibration-free laser-induced breakdown spectroscopy (CF-LIBS) indicated the plasma temperature was about 5000 ± 200 K, obtained from the slope of the Boltzmann plot and an optimal iron/oxygen ratio of 0.769. This research effectively connects the data obtained by RSM with C-F LIBS.